The development of romantic relationships in adolescence (Cambridge University Press, 1999)
Numerous volumes exist on adult romantic relationships and on adolescent sexuality, but this is the first volume to examine adolescent romantic relationships. A group of eminent investigators met to discuss the topic and were charged with the task of writing about their conceptualization of these relationships and of romantic experiences in adolescence. The papers cover the full range of aspects of romantic relationships, and examine general processes and individual differences within the general context of adolescent development. Each paper contains numerous provocative ideas that are designed to stimulate research on the topic